Development of 3D inkjet printing heads for high viscosity fluids - Van Tonder, Petrus Jacobus Malan (My University, 2015)
Opening up local markets for worldwide competition has led to the fundamental change in the development of new products. In order for the manufacturers to stay globally competitive, they should be able to attain and sustain themselves as ‘World Class Manufacturers’. These ‘World Class Manufacturers’ should be able to:  Deliver products in fulfilling the total satisfaction of customers.  Provide high quality products.  Offer short delivery time.  Charge reasonable cost.  Comply with all environmental concern and safety requirements. When a design is created for a new product there is great uncertainty as to whether the new design will actually do what it is desired for. New designs often have unexpected problems, hence prototypes are part of the designing process. The prototype enables the engineers and designers to explore design alternatives, test theories and confirm performance prior to standing production of new products. Additive Manufacturing (AM) technologies enable the manufacturers to produce prototypes and products which meet the requirements mentioned above. However the disadvantage of AM technologies, is that the printing material which is required is limited to that of the supplier. When uncommon printing materials must be used to manufacture a prototype or product, the 3D printing process stood out above the rest owing to its printing method. However the printing heads used in current commercially available 3D printers are limited to specific fluid properties, which limits new and unique powder binder combinations. Owing to the problem mentioned, the need arose to develop a more ‘rugged’ printing head (RPH) which will be able to print with different fluid properties. The RPH could then be used to print using unique and new powderbinder combinations. The RPH was designed and constructed using the solenoid inkjet technology as reference. In order to determine the effect which the fluid properties have on the droplet formation, fourteen different glycerol-water test solutions were prepared. The fluid properties were different for each of the glycerol-water solutions. The fluid properties included the viscosity, density and surface tension of the solution. The control parameters of the RPH were theoretically calculated for each of the glycerol-water solutions and nozzle orifice diameter sizes. The control parameters of the RPH included the critical pressure and time. Using an experimental setup, droplets ejected from the RPH could be photographed in order to be analysed. It was determined that the theoretically calculated critical times could not be used in the RPH, as the pulse widths were much lower than the recommended minimum valve pulse width of the solenoid valve used. The control parameters were then determined practically for each of the different glycerol-water solutions as well as for each nozzle orifice diameter size. The practically determined control parameters were also compared to that of the theoretically determined parameters. A mathematical model was formulated for each of the practically determined critical pressure and time parameters. Non-glycerol-water solutions were also prepared in order to determine whether the control parameters could be calculated using the practically determined mathematical models. It was found that the practically determined mathematical models, used to calculate the control parameters, could not be used with non-glycerol-water solutions. Using the practically determined mathematical models, the drop formation process of the non-glycerol-water solutions was not optimized and satellite droplets occurred. Although the practically determined models did not work for non-glycerol-water solutions, the methods used to determine the control parameters for the glycerol-water solutions could still be used to determine the practical critical pressure and time for Newtonian solutions.
D. Tech. (Department of Electronic Engineering, Faculty of Engineering and Technology) --Vaal University of Technology
Keywords: World class manufacturers; Prototypes; Additive manufacturing technologies; Rugged printing head; 3 D printing; Three dimensional printing; Solenoid inkjet; 686.233; Three-dimensional printing